Computational Analysis of Wall Shear Stress Patterns on Calcified and Bicuspid Aortic Valves: Focus on Radial and Coaptation Patterns - Huseyin Enes Salman; Levent Saltik; Huseyin C. Yalcin (Fluids, 2021)
Calcification and bicuspid valve formation are important aortic valve disorders that disturb the hemodynamics and the valve function. The detailed analysis of aortic valve hemodynamics would lead to a better understanding of the disease’s etiology. We computationally modeled the aortic valve using simplified three-dimensional geometry and inlet velocity conditions obtained via echocardiography. We examined various calcification severities and bicuspid valve formation. Fluid-structure interaction (FSI) analyses were adapted using ANSYS Workbench to incorporate both flow dynamics and leaflet deformation accurately. Simulation results were validated by comparing leaflet movements in B-mode echo recordings. Results indicate that the biomechanical environment is significantly changed for calcified and bicuspid valves. High flow jet velocities are observed in the calcified valves which results in high transvalvular pressure difference (TPG). Wall shear stresses (WSS) increased with the calcification on both fibrosa (aorta side) and ventricularis (left ventricle side) surfaces of the leaflet. The WSS distribution is regular on the ventricularis, as the WSS values proportionally increase from the base to the tip of the leaflet. However, WSS patterns are spatially complex on the fibrosa side. Low WSS levels and spatially complex WSS patterns on the fibrosa side are considered as promoting factors for further calcification and valvular diseases.